Examining Transdiagnostic Vulnerabilities among HIV Positive Smokers Seen at Three Inner City Community Based Organizations - Lubetkin, Erica I. (AIDS Care, 2017)
Investigators have proposed a “transdiagnostic vulnerability framework” that examines the relationship between smoking and broader emotional factors, including anhedonia, anxiety sensitivity, and distress tolerance. Because smoking and depression are more common in persons living with HIV and AIDS (PLWHA) than in the general population, understanding the relationship between smoking and mental health is critical. The following study aims to characterize levels of clinically significant depressive symptoms and these broader emotional factors as well as the relationship between these factors and smoking-related variables in a sample of PLWHA. This cross-sectional study employed convenience sampling to survey adult clients who attended one of three AIDS service organizations in New York City. The questionnaires assessed sociodemographic and HIV health care variables, tobacco use, and anxiety- and depression-related constructs. 150 PLWHA completed surveys. Among the 118 smokers, the prevalence of clinically depressive symptoms was 53%. Participants with clinically significant depressive symptoms had significantly higher mean anhedonia scores and anxiety sensitivity scores and lower mean distress tolerance total scores compared to participants without clinically significant depressive symptoms (p<0.001). Smoking cessation treatment for persons with co-morbid psychiatric disorders has been suboptimal and treatment for co-morbid mental health conditions tends to align with disorder-specific treatment. Given that PLWHA are a priority population, further research should address how to best tailor interventions to a group with multiple obstacles to successful tobacco cessation.